Assessment of Trace Element Levels in Muscle Tissues of Fish Species Collected from a River, Stream, Lake, and Sea in Sakarya, Turkey - Tülay Küpeli; Hüseyin Altundağ; Mustafa İmamoğlu (The Scientific World Journal)
Levels of some trace and essential elements, including Al, B, Ba, Cr, Cu, Fe, Mn, Ni, Sr, and Zn, were determined in 17 different fish species from Sakarya River, Çark Stream, Sapanca Lake, and Western Black Sea using ICP-OES after microwave (MW) digestion procedure. During preparation of samples for analysis, wet and MW digestion methods were also compared. Accuracy of the digestion methods was checked by the analysis of DORM-3 reference material (Fish Protein Certified Reference Material for Trace Metals). Concentrations of trace elements were found as Al: 6.5–48.5, B: 0.06–3.30, Ba: 0.09–2.92, Cr: 0.02–1.64, Cu: 0.13–2.28, Fe: 7.28–39.9, Mn: 0.08–11.4, Ni: 0.01–26.1, Sr: 0.17–13.5, and Zn: 11.5–52.9 µg g−1. The obtained results were compared with other studies published in the literature. Trace element levels in various fish species collected from waters in Sakarya region were found to be below limit values provided by Turkish Food Codex (TFC), Food and Agriculture Organization (FAO), and World Health Organization (WHO).